PERSEPSI MASYARAKAT KECAMATAN TAMBANG TERHADAP KEPEMIMPINAN JEFRY NOER SEBAGAI BUPATI KAMPAR PERIODE 2011-2016 - Renny Noer Fajri Noer Fajri; Gimin '; Sri Erlinda Erlinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Community Mine districts still receive less attention from the government led by Jeffery Noer, consequently making the various elements of society disappointed over his leadership. So that the public is entitled to view or perception of how the type of leadership a leader, also gives the perception of how the leadership qualities of the leader. This study aims to determine the District Public Perception of Leadership Against Mine Jefry Noer As Kampar Regent period of 2011-2016. Sampling technique used purposive sampling techniques and sample area and selected respondents were people aged over 20 years and above, as many as 170 people. Data were collected through observation, questionnaires and technical literature. Analasis data using a combination of research methods (Mixing reasearch) The results of research show that public perception of the mining districts Jefry Noer's leadership as Kampar Regent period 2011-2016 from the aspect of the type of leadership is an autocratic leader as much as 67.4%. Under the leadership traits as Kampar Regent  Jefry Noer has properties that are less good leader because the mnjawab "less Agree" as much as 66.9%. Then it can be concluded that the public perception of the mining districts Jefry Noer’s leadership as Kampar Regent 2011-2016 period that is less good. Keywords: Perception; community; leadership